For the good of the party, for the good of the nation: Ingroup projection can motivate support for political violence - Waddell, M. W.; Wright, S. C.; Waldzus, S.; Stebner, G. A. (Frontiers in Social Psychology, 2024)
Support for political violence in the United States appears to be growing. We outline a model that positions ingroup projection—seeing ingroup values as the shared values of a larger inclusive societal group—as a key psychological process through which identification with political ingroups (Democrats/Republicans) and with national superordinate categories (Americans) influence support for political violence. We tested this model in two studies. Study 1 (N = 297) included original survey data collected during the 2016 US Presidential election, and analyses revealed that identification with Democrats or Republicans and identification with Americans both had positive indirect effects on support for political violence that were mediated by ingroup projection. Study 2 (N = 642) provided a preregistered replication of these results using original data collected during the 2022 US Midterm Senate elections. These results provide insight into the psychological processes that underlie support for political violence in the United States and elucidate a generalizable model for understanding destructive intergroup behaviors in a variety of real-world intergroup contexts.